PENGAJARAN TERBENTUKNYA HARGA PASAR DALAM PEREKONOMIAN KELAS XI DI SMK DEWI SARTIKA JAKARTA BARAT - Puteri, Annisa Fadila; Chelsya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The teaching assistance activity program in educational units aims to increase students' understanding of the Dewi Sartika Vocational School, West Jakarta, about the economy in Indonesia in terms of the formation of market prices in the economy. Teaching assistance activities in educational units start from 07 August 2023 – 30 November 2023. MBKM teaching activities in the author's educational unit are accompanied by Mrs. Chelsya. The author provides training in the form of example questions and practice questions for students. The benefits felt during assistance activities in this educational unit are becoming yourself to appear confident in speaking in front of many people, getting to know and understanding the character and personality of each person so that it can be a provision for writers when they are directly involved in the world of work, training writers to have a higher spirit of socialization, and increase patience for writers in understanding the attitudes, character and personality of each person so that it can become a provision for internal writers. As a result of MBKM teaching activities in educational units, students can understand market price material in the economy and basic accounting material as a whole.